A Convexity Concept with Respect to a Pair of Functions. (23rd May 2022) - Samet, Bessem
Abstract: In this paper, the concept of a convex function with respect to a pair of functions is introduced. Then some properties related to this notion are established. Furthermore, some fundamental inequalities from the theory of convex functions are extended to this new class of mappings.